Vancomycin Utilization Evaluation in a Major Teaching Hospital in West of Iran - Sajad Khiali; Samira Eskandari; Hadi Hamishehkar; Parham Maroufi; Haleh Rezaee (Research Center for Rational Use of Drugs (RCRUD), 2020)
Background: Drug utilization review is defined as an authorized, structured, ongoing review of prescribing, dispensing and use of medication. Vancomycin is a narrow-spectrum glycopeptide anti-infective with activity against many gram-positive organisms such as Staphylococci, group A